Predictive Value of Biochemical Markers CRP, WBC, and Total Cholesterol for Postoperative Dry Eye Syndrome Following Phacoemulsification Cataract Surgery: Validating CRP, WBC, TC for Dry Eye Post-Phacoemulsification - Wang, Yenan; Wang, Xizhe; Li, Zhen; Yang, Huiqing; Zhang, Xuxiang (Journal of Medical Biochemistry, 2025)
Background: Dry eye syndrome is a common complication following phacoemulsification cataract surgery, potentially influenced by systemic biochemical factors. This study aimed to evaluate the predictive efficiency of three routinely measured biochemical markers—C-reactive protein (CRP), white blood cell count (WBC), and total cholesterol (TC)—in identifying patients at risk for postoperative dry eye syndrome.Methods: A total of 87 patients undergoing phacoemulsification between January 2024 and February 2025 were enrolled and categorized into dry eye (n=49) and non-dry eye (n=38) groups. Blood samples were collected preoperatively to assess CRP, WBC, and TC levels using standard laboratory protocols. Baseline characteristics were compared, and multivariate logistic regression was conducted to identify independent risk factors. Receiver operating characteristic (ROC) curves were generated to determine the predictive performance of each marker and their combination.Results: Patients in the dry eye group exhibited significantly elevated CRP, WBC, and TC levels compared to the non-dry eye group (P
Keywords: C-reactive protein; White blood cell count; Total cholesterol; Biochemical markers; Cataract surgery; Dry eye syndrome; Predictive diagnostics